DI Hya: A Near-contact Binary with a Close-in Companion. (7th February 2017) - Liao, W.-P.; Qian, S.-B.; Li, L.-J.; Zhou, X.; Zhao, E.-G.; Zhang, J.
Abstract: DI Hya is a short-period eclipsing binary and its classification has been discussed by several authors. New four-color light curves were obtained and have been analyzed together with the data from Manimanis & Niarchos simultaneously using the W–D method. The binary turns out to be a near-contact system where both components are filling or nearly filling their critical Roche lobes. The secondary has a temperature difference of Δ T ≃ −2800 K. The orbital period investigation has been ignored so far. All charge-coupled devices (CCD) and pe times of light minima are used for period analysis, showing that a cyclic variation with a short period of 1.46 years and a small semi-amplitude of 0.0034 days and a downward parabolic variation with a rate of P ͘ = − 2.98 ( ± 0.32 ) × 10 − 7 days yr − 1 . The short period and small semi-amplitude cyclic variations were analyzed for the light-travel time effect via the presence of a close-in tertiary binary with an orbital separation shorter than 1.57(±0.31) au. Orbital properties of this close-in companion should provide valuable information on the formation of this short-period binary and stellar dynamical interaction. The downward parabolic change may be caused by angular momentum loss via an enhanced stellar wind of the more evolved secondary star.